Hexarelin treatment preserves myocardial function and reduces cardiac fibrosis in a mouse model of acute myocardial infarction. Issue 9 (13th May 2018) - McDonald, Hayley; Peart, Jason; Kurniawan, Nyoman; Galloway, Graham; Royce, Simon; Samuel, Chrishan S.; Chen, Chen
Abstract: Ischemic heart disease (IHD) is a leading cause of morbidity and mortality worldwide. Growth hormone secretagogues (GHS) have been shown to improve cardiac function in models of IHD. This study determined whether hexarelin (HEX), a synthetic GHS, preserves cardiac function and morphology in a mouse model of myocardial infarction (MI). MI was induced by ligation of the left descending coronary artery in C57BL/6J mice followed by vehicle (VEH; n = 10) or HEX (0.3 mg/kg/day; n = 11) administration for 21 days. MI‐injured and sham mice (treated with VEH; n = 6 or HEX; n = 5) underwent magnetic resonance imaging for measurement of left ventricular (LV) function, mass and infarct size at 24 h and 14 days post‐MI. MI‐HEX mice displayed a significant improvement ( P < 0.05) in LV function compared with MI‐VEH mice after 14 days treatment. A significant decrease in LV mass, interstitial collagen and collagen concentration was demonstrated with chronic HEX treatment (for 21 days), accompanied by a decrease in TGF‐ β 1 expression, myofibroblast differentiation and an increase in collagen‐degrading MMP‐13 expression levels. Furthermore, heart rate variability analysis demonstrated that HEX treatment shifted the balance of autonomic nervous activity toward a parasympathetic predominance and sympathetic downregulation. This was combined with a HEX‐dependent decrease in troponin‐I, IL‐1 β and TNF‐ α levels suggestive of amelioration of cardiomyocyte injury. These results demonstrate that GHS may preserve ventricular function, reduce inflammation and favorably remodel the process of fibrotic healing in a mouse model of MI and hold the potential for translational application to patients suffering from MI. Abstract : Hexarelin therapy improves left ventricular function and reduces infarct size in a mouse model of myocardial infarction. This study provides insight into the antifibrotic effects of hexarelin and suggests that hexarelin may represent a prevent inflammation, adverse remodeling and left ventricular dysfunction following acute myocardial infarction in a mouse model.